Engineering students or student engineers? - Lindsay, Euan; Munt, Roger; Rogers, Helen; Scott, David; Sullivan, Karen (CQUniversity, 2008)
This paper reports on an innovative unit that embeds the acquisition of communication and professional skills into a technically based project. The project revolves around two engineering artefacts: a popsicle-stick bridge and a mousetrap-powered car. The design and construction of each artefact are conducted by different teams of students – each team designs a bridge and constructs a car, or vice versa. The core principle behind this approach is requiring the students to act as Student Engineers, rather than as engineering students. Requiring students to work both as designers and constructors introduces them to the different communication requirements of each role. More powerfully, they also portray the role of the clients for each others’ engineering project, providing a valuable alternative perspective. The project has led to significant improvements in students’ communication skills as well as their development of their identities as professional engineers.